Hubungan Dukungan Sosial dengan Tingkat Depresi pada Remaja di SMA Negeri 2 Semarang - Arina Laila Fauziyya; Nutrisia Nu’im Haiya; Iwan Ardian (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Adolescents are a vulnerable age group when it comes to mental health disorders, one of which is depression. Depression in adolescents can be influenced by various factors, one of which is social support. Good social support from family, friends, and the surrounding environment plays an important role in maintaining the emotional stability of adolescents so that they can avoid depression. This research method is a quantitative study with a cross-sectional approach. The sample consisted of 108 student respondents using total sampling technique. Data collection was conducted using a social support questionnaire and a depression level questionnaire (Hamilton Depression Rating Scale), which were then analyzed using Spearman's rank correlation test. The results showed that most respondents were 17 years old and received good social support. The depression level was in the normal category for 106 respondents. The Spearman Rank test results showed a p-value of 0.006 (p<0.05). The conclusion is that there is a significant relationship between social support and depression levels among adolescents at SMA Negeri 2 Semarang. The better the social support received, the lower the depression levels experienced by adolescents.